Creative Leadership of School Administrators Affecting Teachers’ Abilities to Develop a Learning Management Innovation in the Narathiwat Primary Educational Service Area Office 1 - Enor, Haayirosmeenee; Maitreephun, Warapark (Journal of Information and Learning [JIL], 2023)
The objectives of this research were to determine 1) the level of creative leadership of school administrators, 2) the level of teachers’ abilities to develop a learning management innovation, 3) the relationship between the creative leadership of school administrators and the teachers’ abilities to develop a learning management innovation, and 4) the predictive variables of creative leadership of school administrators that affect teachers’ abilities to develop a learning management. The sample of this study included school directors, head teachers of academic affairs, and teachers who currently developed learning management innovations, a total of 327 informants. The unit of this study was at the school level. By using the Yamane formula, 109 schools became sample sites. The research instrument was a five–level rating scale questionnaire with a reliability of 0.986. The data were analyzed using mean, percentage, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The results showed that 1) the creative leadership of the school administrators was at a high level (M = 4.38, SD = .478), that 2) the teacher’s ability to develop learning management innovations was at a high level (M = 4.20, SD = .478), that 3) the creative leadership of the school administrators was positively correlated with the teachers’ ability to develop learning management innovations at a relatively high level (rX,Y = .626) with a statistically significant level at the .01, and that 4) the creative leadership of school administrators affected teachers’ learning management innovation development ability. There were only two predictive variables: ’flexibility in adaptation’ was the best predictor with statistical significance at the .01 level, followed by ’vision for change with statistical significance at the .05 level, which predicted teachers’ ability to develop innovative learning management.